The Influence of Youtube Video in Learning English (A Case Study of 3 Years Old Child in Medan) - Zulhantiar, Putri Annisa; Mawarni, Nidiya; Br. Perangin-angin, Alemina (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to describe and find the influences of YouTube in second language acquisition that occurs in 3 years old child in Medan. The method used is a descriptive with a listening and recording technique. Through this study, the author can find out and gain knowledge about the process of language acquisition that occurs in early childhood. The findings of this study, which were observed in four speech events: naming colors, recognizing animals, recognizing body parts, and naming fruits, highlight the influences of repetition, reinforcement, and visual cues, all of which are at the heart of behaviorist learning.